2010
DOI: 10.1162/rest_a_00034
|View full text |Cite
|
Sign up to set email alerts
|

Corruption and Bilateral Trade Flows: Extortion or Evasion?

Abstract: We analyze the impact of corruption on bilateral trade, highlighting its dual role in terms of extortion and evasion. Corruption taxes trade, when corrupt customs officials in the importing country extort bribes from exporters (extortion effect); however, with high tariffs, corruption may be trade enhancing when corrupt officials allow exporters to evade tariff barriers (evasion effect). We derive and estimate a corruption-augmented gravity model, where the effect of corruption on trade flows is ambiguous and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(65 citation statements)
references
References 40 publications
5
60
0
Order By: Relevance
“…Building on the work of Helpman et al (2008) and Dutt and Traca (2010), we use a common religion index and a measure of remoteness as instruments, along with lagged values, in an attempt to overcome this problem. The estimated coefficients are reported in column 2 of Table 4.…”
Section: Econometric Issues and Empirical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Building on the work of Helpman et al (2008) and Dutt and Traca (2010), we use a common religion index and a measure of remoteness as instruments, along with lagged values, in an attempt to overcome this problem. The estimated coefficients are reported in column 2 of Table 4.…”
Section: Econometric Issues and Empirical Resultsmentioning
confidence: 99%
“…Dutt and Traca (2010) used bilateral trade data over the sample period 1982 and 2000, covering 128 exporters and 126 importers, and found that the effect of corruption is ambiguous and depends upon the level of trade protection in the economy. While corruption generally hinders trade, a positive relationship appears as the government-erected barriers to trade rise.…”
Section: Model Specification and Data Descriptionmentioning
confidence: 99%
“…The consensus in the literature is that corruption is detrimental for a country, and its negative consequences are consistently found in relation to key economic indicators such as GDP growth, trade, productivity, or foreign direct investment (Cuervo-Cazzura, 2008;Anokhin & Schulze, 2009;Dutt & Traca, 2010). In contrast, there are significant gaps in our understanding of the consequences of bribing for firm strategies (Galang, 2012;CuervoCazurra, 2016), and in particular for innovative performance (Mueller et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies support this conjecture and find negative effects on economic growth (Mauro, 1995), productivity (Asiedu & Freeman, 2009;de Rosa, Gooroochurn, & Gorg, 2010), trade (Dutt & Traca, 2010), foreign investments (Cuervo-Cazurra, 2006), entrepreneurship (Anokhin & Schultze, 2009), and social development (Rose-Ackerman, 1998). In contrast, an opposite view in the literature argues for positive effects of corruption, especially in weak institutional settings (Meon & Weill, 2010;de Vaal & Ebben, 2011) where the costs of preventing it usually outweigh the benefits (Acemoglu & Verdier, 2000).…”
Section: Bribery: Grease or Sand To Economic Activities?mentioning
confidence: 94%
“…The fact that countries like Russia, Saudi Arabia, Mexico and India which score only rank 105, 48, 61 and 96 in the so called Enabling Trade Index in the year 2014 are among the most important global traders, raises concern about the long debated link between countries' institutions and their trading activity. This mismatch suggests that institutions and democracy are not uniquely positively interlinked with trade as some studies suggest (Yu (2010), Francois and Manchin (2013), Dutt and Traca (2010)). Apart from Russia, another prominent example is China, which became the biggest trading nation in the world over time.…”
Section: Introductionmentioning
confidence: 96%